Oar-miR-16b and oar-miR-27a: negatively correlated with milk yield and milk protein in sheep - Duman, Esra; Ozmen, Ozge; Kul, Selim (Taylor & Francis Inc, 2022)
The characterization of miRNAs from sheep milk and their effect on milk yield and composition in sheep are remain unclear. Therefore, the aim of this study was to determine the expression pattern of several important miRNAs, which are associated with lactation in the sheep milk between high and low lactating-yield ewe groups. In addition to experimentally obtained miRNA expression results, the miRNA target genes were determined by bioinformatics analysis to identify biological pathways involved. miRNAs found to differ significantly in the expression level between the groups were oar-miR-181a, oar-miR-23a, oar-miR-27a, oar-miR-16b and oar-miR-374. Also, oar-miR-27a was shown negative correlation with milk protein and lactose contents while oar-miR-16b was shown negative correlation with milk yield in the high milk yield group. The highest connected hub genes for miR-27a target genes were determined as MAPK14 and PPARG. Also, six genes (HSPA4L, DNAJA2, ATP6V1B2, PPP2R1A, PPP2R1B, and PRKAR2A) were detected as hub genes for miR-16b. In this study, the relationship between expression profiles of several important miRNAs in sheep milk and milk yield and milk composition were investigated for the first time in high and low lactating yield groups.
Keywords: Milk; microRNA (miRNA); dairy sheep; lactation; milk yield; milk protein